The machinic city : Media, performance and participation - Dias P. Marcos (Book collections on Project MUSE., 2021)
The machinic city reveals the potential of performance art to create spaces for reflection and deliberation on contemporary urban living and to speculate on the future of cities. It analyses several case studies of performance art that foreground new modes of subjectivity emerging from hybrids of human and machine agency.